Development of Czech Film Poster over the Years 1990-2012 - Šafaříková, Kateřina; Hanzlík, Jan (Iluminace, 2013)
An analysis of the development of the Czech film poster in the period after 1989, when it had to adapt to the free market and new possibilities of processing.
Keywords: film posters; film marketing; film market; advertising